2018
DOI: 10.4103/ijnmr.ijnmr_36_16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hope therapy on the mood status of patients with diabetes

Abstract: Background:Diabetes mellitus (DM) is a chronic disease which imposes high costs on patients and society and results in complications in patients. One of these complications includes issues related to mood. Thus, the present study was conducted with the aim to determine the effect of hope therapy on the mood status of patients with DM.Materials and Methods:This quasi-experimental study was performed with two groups in three stages in the summer of 2015 on 38 individuals. The study population consisted of all in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…Results of the study conducted by Ghazavi et al is consistent with those of present study and they showed that hope therapy in patients with diabetes increased hope in intervention group compared to control group [7]. In addition, the study conducted by Khoshnoud et al indicated that education of life skills increased significantly happiness and hope of patients with type II diabetes [19].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Results of the study conducted by Ghazavi et al is consistent with those of present study and they showed that hope therapy in patients with diabetes increased hope in intervention group compared to control group [7]. In addition, the study conducted by Khoshnoud et al indicated that education of life skills increased significantly happiness and hope of patients with type II diabetes [19].…”
Section: Discussionsupporting
confidence: 89%
“…Reduction of happiness in diabetic patients may be one of disease effects resulting from stressful nature of disease. As a result, hope therapy will help such patients to cope with this disease [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with the patient's disease (Ghazavi et al, 2015) and living with MS requires continuous adaptation to cope with the unpredictable symptoms (Anderson, Turner & Clyne, 2016). Hope is an important resource for people with MS to cope with multiple lesions of this disease.…”
Section: Introductionmentioning
confidence: 99%